Michael Graves
Contiene: PROYECTS: Cincinnati Symphony Summer Pavilion. Ohio 1983- / St. James Townhouses. Ohio 1982- / The Republic Building. Texas 1982- / The Humana Building. Kentucky 1982- / Art History Departament. New York 1981- BUILDINGS: Public library. California 19880-83 / Environmental education centers. New Jersey 1980-83 / The Portland building. Oregon 1980-1982.
Keywords: PABELLONES; MUSICA; VIVIENDAS ADOSADAS; EDIFICIOS DE OFICINAS; EDIFICIOS EN ALTURA; BIBLIOTECAS; ARQUITECTURA EDUCACIONAL; ESTADOS UNIDOS; OREGON; NEW JERSEY; CALIFORNIA; NEW YORK; KENTUCKY; TEXAS; OHIO; GRAVES, MICHAEL